Permeability and charge-dependent adsorption properties of the S-layer lattice from Bacillus coagulans E38-66. - Sára, M (1992)
We investigated the permeability properties of the oblique S-layer lattice from Bacillus coagulans E38-66 after depositing cell wall fragments on a microfiltration membrane, cross-linking the S-layer protein with glutaraldehyde, and degrading the peptidoglycan with lysozyme. Comparative permeability studies on such multilayered S-layer membranes and suspended S-layer vesicles from thermophilic members of the family Bacillaceae with use of the space technique (M. Sára and U. B. Sleytr, J. Bacteriol. 169:4092-4098, 1987) revealed identical molecular exclusion limits (M. Sára and U. B. Sleytr, J. Membr. Sci. 33:27-49, 1987). Examination of the S-layer lattice from B. coagulans E38-66 with the S-layer membrane technique revealed unhindered passage for molecules up to the size of myoglobin (M(r) 17,000). The molecular dimensions of this protein (2.8 by 3.2 by 4.5 nm) correspond approximately to the size of the ovoid-shaped pore previously shown by high-resolution electron microscopy of negatively stained S-layer self-assembly products (D. Pum, M. Sára, and U. B. Sleytr, J. Bacteriol. 171:5296-5303, 1989). Chemical modification of the S-layer protein and comparative labeling, adsorption, and permeability studies clearly demonstrated that (i) in the native state, free amino and carboxyl groups are present on the outer S-layer face and in the interior of the pores and (ii) electrostatic interactions between these groups prevent unspecific adsorption of the S-layer in vivo.